Contribution of TPACK for a Pedagogical Capability in the Vocational Pre-service Teachers for Electrical Engineering Education - Setiadi Cahyono Putro; Wahyu Nur Hidayat; Mahfud Jiono; Ahmad Mursyidun Nidhom; Junaidi Syarif (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
The objective of this study was to reveal the correlation and contribution of Technological Pedagogical Content Knowledge (TPACK) for a pedagogical capability of vocational preservice teachers. The research method used quantitative with a descriptive correlational research design. The research sample consisted of electrical engineering undergraduate students in the Faculty of Engineering at Universitas Negeri Malang. The total samples implemented in this study were 135 students. The data collection used a questionnaire and documentation technique. The reliability of the TPACK questionnaire instrument was 0.972 (Alpha Cronbach). The analysis data technique used the analysis of simple regression. The results of the study revealed a positive correlation and a significant correlation between TPACK and Pedagogical Capability with R = 0.757 (psig 0.000 0.05). The contribution of TPACK to Pedagogical Capability in the Vocational Preservice Teacher was R2 = 0.573.